2004
DOI: 10.1080/15376520490434683
|View full text |Cite
|
Sign up to set email alerts
|

Sulfurtransferases and Cyanide Detoxification in Mouse Liver, Kidney, and Brain

Abstract: The activity of rhodanese, 3-mercaptopyruvate sulfurtransferase (MPST) and cystathionase in mouse liver, kidney, and four brain regions: tele-, meso-, di- and rhombencephalon was studied 30 min and 2 h following a sublethal dose of cyanide (4 mg/ kg body weight) intraperitoneal injection. Simultaneously, sulfane sulfur levels and total sulfur content, a direct or indirect source of sulfur for CN(-) conversion to SCN(-), were also investigated in these tissues. In the liver this dose of cyanide seemed to impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 21 publications
1
63
1
Order By: Relevance
“…The cyanide poisoning can cause reactions such as seizures, tachycardia followed by prostration 14 ; similar reactions were observed in this experiment after the animals were exposed to cyanogenic chemotherapy, showing once again the ability of cyanide to diffuse through the tissues, promoting its toxic action in the brain of these animals which are more susceptible tissues to the action of cyanide 1 .…”
Section: Discussionsupporting
confidence: 48%
“…The cyanide poisoning can cause reactions such as seizures, tachycardia followed by prostration 14 ; similar reactions were observed in this experiment after the animals were exposed to cyanogenic chemotherapy, showing once again the ability of cyanide to diffuse through the tissues, promoting its toxic action in the brain of these animals which are more susceptible tissues to the action of cyanide 1 .…”
Section: Discussionsupporting
confidence: 48%
“…After centrifugation at 1,600× g for 10 min, the supernatant was used for the determination of the activity of sulfurtransferases (mercaptopyruvate sulfurtransferase or MPST, CTH and TST). The activity of MPST was assayed according to method of Valentine and Frankenfeld (1974) with some modifications described by Wróbel et al (2004). CTH activity was determined according to Matsuo and Greenberg (1958) as modified by Czubak et al (2002).…”
Section: Methodsmentioning
confidence: 99%
“…CTH activity was determined according to Matsuo and Greenberg (1958) as modified by Czubak et al (2002). TST (rhodanese) activity was assayed by the method of Sörbo (1957) as described by Wróbel et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…23 Wrobel et al showed that there is difference in 3-MPST activity amongst liver, kidney and brain in mice. 31,32 However, there are no published reports showing the 3-MPST activity in different organs from human or rabbit. One of us (SP) at University of Minnesota measured the specific activity of 3-MPST from liver, kidney, and blood in human and rabbit and found that the 3-MPST activity in rabbit is close to that in humans (unpublished).…”
Section: Discussionmentioning
confidence: 99%